Synthesis and Optical Properties of Polyimide-Silica Hybrid Thin Films - Chang, Chao-Ching; Chen, Wen-Chang (Chemistry of materials, 2002)
In this study, two series of the polyimide−silica hybrid optical thin films, PMDA−ODA/SiO2 and 6FDA−ODA/SiO2, were synthesized using an in situ sol−gel reaction combined with spin coating and multistep curing. The hybrid thin films were prepared by the aminoalkoxysilane-capped poly(amic acid)s and tetramethoxysilane (TMOS) as the precursors. Highly transparent hybrid thin films were obtained at a silica content as high as 54.9 wt %. The FE-SEM study suggests the nanosize domain of the silica moieties in the hybrid thin films. The AFM study demonstrates that the hybrid thin films have excellent planarity. The prepared hybrid thin films show good thermal stability. The refractive indices of the prepared hybrid thin films decrease linearly with increasing silica content while the Abbe number of the hybrid thin films shows the opposite trend. The birefringence of the prepared polyimide−silica hybrid thin films is reduced by incorporating the silica moiety. Optical planar waveguides were prepared from the prepared hybrid thin films using a thermal oxide as the cladding layer. The optical losses of these planar waveguides at 1310 nm are in the range of 0.5−1.9 dB/cm, which are due to the higher harmonics of the aromatic C−H vibration, the O−H vibration, and the extrinsic loss. The optical losses of the prepared polyimide−silica hybrid films are lower than their parent polyimdes and thus have potential applications in optical devices.